Study on fish scales and its systematic approach on colouring process / Rusmawati Ghazali - Ghazali, Rusmawati (2007)
This research has been initiated to assist the fish scales entrepreneur in Malaysia into getting a consistent fish scales dye process. Several tests on colouring dyes have been conducted to establish a suitable dye with consistent measuring techniques. With the above objectives in mind, the researcher hoped to establish a colour guideline in form of colour tones thus provides a wider choice of colour selection to these entrepreneurs. John Snapper or Golden Snapper " Jenahak" from (Lutjanus johni family), Malabar Red Snapper "Merah" from (Lutjanus malabaricus family), Threadfish Bream" Kerisi" from (Nemipteridae family) and Herring or Toli Shad" Terubok" from (Clupeidae family) were the four types of salt water fish selected for their scales for this research as they are the most caught by Malaysian fishermen. In the early stage of this experiment the researcher tried to find a suitable cleaning substance and process to wash these fish scales. Three types of cleaning agent were then tested such as detergent, lime juice and bleach. Ofthe three, lime juice produced the best result. Some other experiments conducted were the crushing test, burning test, pounding test and baking test. They are to determine the durability quality of these fish scales. The fish scales were then tested for colouring suitability. Five different types of fabric dyes were selected such as disperse dye, reactive dye, vat dye, pigment dye and natural dye. Out of these five types, Cool Reactive dye from Remazol brand gave the best colour reaction on these scales. The weighing technique was then established using grams for colours and litre for measuring water. Prior to this the researcher had used a spoon for measuring the colour quantity and cups for measuring the amount of water where it produced an inconsistent colour tones.Based on the colour tones obtained from the experiments, the researcher were able to establish an array ofcolours in the form of colour codes. A colour fastness test were conducted on these coloured scales using test methods such as rubbing test, daylight test and soaking in sulphuric acid. Apart from the above discoveries, the researcher was also able to find other valuable information to be shared with. They include the size, shape, thickness and texture of the scales which were different for all the four types of fish. The resilient characteristic of the scales made it difficult to tear or crushed. However, the colour absorption on these fish scales is being influenced by its thickness. As for the recommendation, this research can be used as reference for producing wider range of handicraft products and products in form ofjewelleries or sequins. The colours can further be experimented using natural dye on other types of salt water or fresh water fish. Batik decoration techniques can be applied on a bigger size fish scales.